Ngunduh Wohing Pakarti: The Moral Roots of Business Governance Principles - Widhianningrum, Purweni; Roekhudin; Prihatiningtias, Yeney Widya (Accounting Department, 2023)
Purpose—This study aims to explore and interpret the moral values of ngunduh wooing Jakarta, which are the basis for forming business governance principles. Design/methodology/approach — This study uses a qualitative method with an interpretive paradigm emphasising a deep understanding of the meaning of ngunduh wohing pakarti in ancient Javanese society. Findings — The moral teaching of ngunduh wohing pakarti is a code of conduct for the ancient Javanese people to manage business activities. The actualization of the moral values ​​as the building of ngunduh wohing pakarti, consisting of balance, honesty, fairness, sincerity, and compassion, is an inspirational signal in formulating the principles of modern business governance today. Practical implications — Ngunduh wohing pakarti can have practical implications for management in carrying out managerial functions so that they can support wise business decision-making processes without harming other parties. The consistent application of governance principles in the moral corridor can provide added value for stakeholders and maintain a sustainable business growth process. Originality/value — This study explores the historical portrait of the development of business governance in Indonesia, especially in the ancient Javanese period. It interprets the moral meaning of ngunduh wohing pakarti in business governance principles.